Nilai Nilai Pendidikan Dalam Sunnah Fitrah Mencukur Rambut Ketiak - Fitriana Yasintha; Chadiza Azzahra Lubis; Nabila Azrilia Syahra; Rawdia Tuzahara; Wismanto Wismanto (CV. Aksara Global, 2024)
This research examines the importance of maintaining one's appearance or personal grooming which includes recommendations, including removing armpit hair. This study is included in the literature review, the focus of this study is hadiths related to self-care, the approach applied is maqasid al-syari'ah al-syatibi. In this research, it is stated that a person's appearance is part of beauty and in the Islamic religion, including manners or ethics, as part of natural human habits. This research uses qualitative research methods by using books, magazines and journal articles as the main source for obtaining information which is then codified and expressed in the form of research results. The results of this study show that the benefits of removing armpit hair are maintaining cleanliness and health, so shaving is considered a recommended and preferred action.